Perilaku Konsumen di Era Digital: Analisis Faktor yang Mempengaruhi Keputusan Pembelian pada Platfrom Shopee dan TikTok Shop - Azlinah Dwi Fahirah; Naila Ayu Zahra; Siti Maryam; Tien Rela; Eri Hariyanto; A. Atabik Syifaul Jinan (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2026)
The development of digital technology has significantly transformed consumer purchasing behavior in recent years. Shopping activities that were previously conducted in person have now shifted to e-commerce and social commerce platforms that offer greater convenience, speed, accessibility, and a variety of attractive promotions. Two platforms experiencing rapid growth in Indonesia are Shopee and TikTok Shop, both of which have gained popularity among diverse consumer segments. These platforms not only offer a wide range of products but also provide interactive shopping experiences through features such as promotions, live shopping, consumer reviews, personalized recommendations, and ease of transactions. This situation has led to notable changes in consumers' purchasing decision-making processes and preferences. Factors such as app usability, promotional strategies, consumer trust, social media influence, user engagement, and evolving digital lifestyles are becoming increasingly dominant in determining purchasing decisions. Therefore, this study aims to analyze the key factors influencing consumer purchasing decisions on the Shopee and TikTok Shop platforms in the digital era, as well as to provide deeper insights into consumer behavior in an increasingly digital marketplace.